Chaos Based Image Encryption using Expand-Shrink Concept - Naveenkumar S K; Panduranga H T; Kiran P (International Journal of Informatics and Communication Technology (IJ-ICT), 2014)
Image information security plays a vital role in computing and communication technologies. This paper describes a new concept of expand and shrink to enhance the strength of chaos based image encryption technique. This method consists of both permutations as well as substitution process for image scrambling and encryption. In permutation plain image is shuffled using chaos technique. Input image undergo two times chaos permutation in-between expand and shrink process leads to substitution. Permutation decreases the correlation between the pixel and substitution increases the entropy of encrypted image. Proposed encryption technique works for both gray-scale and color image. From the experiment highly scrambled image is obtained at the end of encryption process. Decryption process employs exactly reverse process of encryption which results in the reconstructed images.